JURISTIC METHODS OF PURIFYING HARAM INCOMES: AN ANALYSIS IN THE CONTEXT OF ISLAMIC BANKS IN MALAYSIA - Yunus, Saidatolakma Mohd; Haneef, Sayed Sikandar al; Kamaruddin, Zuraidah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
This study attempts to articulate juristic mechanisms by which Islamic banks in Malaysia can purge the unlawful income from their assets. An Islamic bank being a modern corporate entity when dealing with people of diverse cultures and conventional business entities, at times, feels the pressure of not being able to stay away from transactions tainted with haram. Islamic banks as a matter of principle should not involve themselves in any unlawful business activities in the process of which they can procure unlawful incomes. A question of how Islamic banks in Malaysia should treat such incomes, both classical and contemporary jurists have proposed their own set of juristic methods. This study recommends the Islamic banks to address the importance of undertaking the purification process of haram income according to Shari’ah.